Preliminary floristic analysis of the major biomes in southern Africa - G. E. Gibbs Russell (Bothalia: African Biodiversity & Conservation, 1987)
Over 24 000 plant taxa are known to occur in the southern African flora, which is extraordinarily rich on a species/area basis. Lists of species and infraspecific taxa recorded for the six major biomes, Fynbos, Savanna,Grassland, Nama-Karoo, Succulent Karoo and Desert, were obtained from the PRECIS specimen database.These lists were analysed by numbers of unique and shared species and infraspecific taxa. by differential occurrence and life forms of large genera, and by differential occurrence of families. Each biome is floristically distinct except Nama-Karoo. The biomes form two main groupings, those with winter rainfall and those with summer rainfall. Succulent Karoo is most similar to Fynbos and Nama-Karoo is most similar to Savanna.